Effects of inter- and intraspecific competition and food availability on shredder invertebrates from an Amazonian stream - Martins, Renato Tavares; Gomes, Eliane Solar; Keppler, Ruth Leila Ferreira; Firmino, Viviane Caetano (Aquatic Sciences, 2022)
Shredders play an important role in leaf decomposition in headwater streams; however, their activities can be affected by irregular leaf availability, shredder density, and interactions between species. We performed two experiments to evaluate the effects of interspecific (InterComp) and intraspecific (IntraComp) competition and food availability on survival and leaf consumption of two shredder species, Triplectides egleri and Phylloicus elektoros, of an Amazonian stream. We hypothesized that: (i) shredder density (InterComp and IntraComp experiments) has a negative effect on shredder survival and leaf consumption due to increase in interactions between individuals (e.g. direct encounters) that will lead to competition; and (ii) low food availability (IntraComp experiment) will increase competition among individuals, decreasing shredder survival and leaf consumption. In both experiments, high densities of shredders caused direct encounters between individuals and led to a decrease in survival and leaf consumption. Moreover, In the IntraComp experiment, lower survival and leaf consumption were observed in treatments with low food availability, probably associated with competitive interactions for limited resources. Our results indicate that decreased food availability, increased shredder density, and inter-and intraspecific interactions lead to competition for food and space, resulting in direct encounters between shredders and the occurrence of events such as cannibalism, and/or can inhibit feeding activities (e.g., avoiding conspecifics), thereby decreasing survival and leaf consumption. © 2022, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Aquatic insects; Cannibalism